The enforcement of the child care centre act 1984 in governing child care centre in Malaysia / Elina Ezzauddin, Ily Zalikha Shahrinan and Norja Abdul Razak - Ezzauddin, Elina; Shahrinan, Ily Zalikha; Abdul Razak, Norja (2012)
Upon realizing that there were so many unsolved cases involving children in the child care centre, we believe that the main problem about this matter is regarding the enforcement of the law in governing the child care centre. The law is in existence however, there is no application of the law towards the operation of child care centre. With the reference to the Child Care Centre Act 1984, we set down the lacking of enforcement of the law in governing the child care centre and seek for the enforcement of law in governing it. This is to prevent those cases involving children to occur again. To achieve the objectives of the study, we have made some comparison between our Child Care Centre Act 1984 with the Queensland Child Care Act 2002 with regards to the enforcement. Besides that, few respondents from different backgrounds have been selected and interviews have been conducted with them. Their knowledge on this matter helps us to identify the issue of lack of enforcement in the child care centre.